Avaliação de sistemas de informação: revisão de publicações científicas no período de 1985-2005 - Fernando Skackauskas Dias (2006)
Analyzing and revising journals of Information Systems Evaluation, was descriptive a framework about the techniques and methods, delineating the main characteristics, constructs, structures, disposition in categories of the variables and key words, as well as the historical course and the methodological tendencies. One can see how difficult is to find solid guidelines on the main methodologies, approaches and trends. It is in this point that places the interest of this research, which means to contribute with an updated framework on the theme of Evaluation Information Systems. In that way a revision and analysis of reports published in the period between 1985 and 2005 were accomplishedby this research, which totalized 105 articles. To elaboration of the methodology research, articles interpretation, disposition in categories of the variables and key word were used the bases of the "Content Analysis", the methods of "Evaluation of Articles in Information Systems" and the bases of the "Outline of Key Word Classification". The outcomes of the research allows to model a context that demonstrates a tendency of the researches for a multidisciplinary approaches, a growing interest in the user's cognitive aspects, focus on the determination of attributes of information quality and the alignment of the systems to the corporate strategies. Therefore, the Information System Evaluation has arisen with new approaches in the main researches centers, building a solid framework and a well delimited investigation object.